Capturing strategic alliance outcomes: an analysis of motives, objectives and outcomes - Hynes, Niki; Mollenkopf, D. (Inderscience Enterprises Ltd., 2008)
Strategic alliances are increasingly important to the overall strategyof firms and may be entered to increase competitive advantage. Strategicalliances can include a wide variety of inter-organisational agreements, with awide range of motives and possible outcomes. Although research suggests thatmore than half of the alliances fail and that measures of outcomes lackconsistency and comparability across the range of alliances. This studyproposes a framework and measure that allows a diverse range of alliances,with a wide range of objectives and outcomes to be evaluated for success orfailure.